Development of Instructional Equipment Based on Cooperative Learning on The Subtopic Modification of Mendelian Ratios - APRILINA, SURYA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Along with the presence of international school, it is needed an english instructional equipment to support the instructional activities. The aim of this research is to develop the appropriate instructional equipment especially on Biology based on cooperative learning on the suptopic Modification of Mendelian Ratios, to know the appropriarity of the instructional equipment, to know the student’s response toward instructional equipment that developed. The development of this instructional equipment is in accordance with 4-D models consisting phases : define, design, develop, disseminate, with no disseminate phase. This research is done in University State of Surabaya and Khadijah Senior High School. The try out is done using 31 students. The object of the research is the instructional equipment. The appropriarity of the instructional equipment is gained from expert analysis and student’s responses toward the instructional equipment. The result of the research shows (1) analysis of the instructional equipment based on cooperative learning on subtopic Modification of Mendelian Ratios is appropriate, (2) there are 3 instructional goals which are not reached, to define the criptomery, to define the polimery ad to find the genotype and phenotype ratio of polimery. (3) result of student’s read toward the worksheet and student’s book show that they can be easily understood by the students from word choice, sentence, and also the content, (4) result of student’s response toward the worksheet and student’s book that used in instructional process show that the worksheet and the student’s book are interesting and can be understood by the students.Keywords : Instructional equipment, Modification of Mendelian Ratios, Cooperative learning